Physicians' perceptions of shared decision‐making for implantable cardioverter‐defibrillators: Results of a physician survey. (25th September 2019) - Ali‐Ahmed, Fatima; Matlock, Daniel; Zeitler, Emily P.; Thomas, Kevin L.; Haines, David E.; Al‐Khatib, Sana M.
Abstract: Background: Centers for Medicare and Medicaid Services has mandated the use of shared decision‐making (SDM) for implantable cardioverter‐defibrillator (ICD) implantation. SDM tools help facilitate quality SDM by presenting patients with balanced evidence‐based facts related to risk and benefits. Perceptions of ICD implantation may differ based on patients' sex and race. Objective: To determine if and how physicians are incorporating SDM in counseling patients about ICD and if they are aware of sex‐ and race‐based differences in patients' perception of ICDs. Methods: This was a pilot study involving an online survey targeting attending physicians who implant ICDs. Physicians were randomly selected by a computer‐based program; 350 surveys were sent. Results: Of the 124 (35%) respondents to the survey, 102 (84%) met the inclusion criteria, and of those, 99 (97%) were adult electrophysiologists. Most physicians (90, 88%) stated they engaged in SDM during the general consent process. Sixty‐three (62%) physicians discuss end of life issues while obtaining general consent. Forty‐four (43%) physicians said they use an existing SDM tool with the Colorado SDM tool being the most common (39, 89%). The majority of physicians were unaware of sex‐ and race‐based differences in perceptions related to ICD implantation (sex 64, 63% and race 63, 62%). Conclusion: A vast majority of physicians are engaging in SDM; however less than half are using a formal SDM tool, and a minority of physicians were aware of sex‐ and race‐based differences in patients' perception of ICD implantation. Sex‐ and race‐based tools might help address this gap.